Transação em matéria tributária: análise do instituto e de sua aplicabilidade a partir da edição da lei 13.988/20 - Castilho, Mateus José (2021)
This article, based on research that used the descriptive method with bibliographic research, seeks to study the legal basis and applicability of the legal institute of tax transaction, provided for in articles 156, III, and 171 of the National Tax Code. For the study of this theme, the concept of transaction in tax law was addressed, based on doctrinal studies, as well as the purpose of the institute regarding the termination of litigation with the State. For this reason, this article intends to consider whether the tax transaction is an effective institute to resolve conflicts between the parties and relieve the judiciary and the public machine? In this way, the concept of tax credit, the unavailability of the public good and the termination of litigation, assistance from the doctrine and analysis of laws and ordinances in force, as well as the transaction operation between the agents of the tax process were analyzed. We sought to analyze and expose some tools that the State can have in order to achieve the public interest. Thus, the main objective of this work is to demonstrate and encourage the application of the tax transaction under the terms already provided for by article 171 of the National Tax Code, as well as demonstrate that Law 13.988/2020 supported the public agent so that they can carry out the legal business in compliance with the principles of public administration.